Surgical repair of tetralogy of Fallot using autologous right atrial appendages: short- to mid-term results. (9th November 2020) - Amirghofran, Ahmadali; Edraki, Fatemeh; Edraki, Mohammadreza; Ajami, Gholamhossein; Amoozgar, Hamid; Mohammadi, Hamid; Emaminia, Abbas; Ghasemzadeh, Bahram; Borzuee, Mohammad; Peiravian, Farah; Kheirandish, Zahra; Mehdizadegan, Nima; et al.
Abstract: OBJECTIVES: The prevention of pulmonary insufficiency (PI) is a crucial part of the tetralogy of Fallot repair. Many techniques have been introduced to construct valves from different materials for the right ventricular outflow tract, including the most commonly constructed monocusp valves. We are introducing a new bicuspid valve made intraoperatively using the autologous right atrial appendage (RAA) to prevent PI in these patients. METHODS: The RAA valve was constructed and used in 21 patients with tetralogy of Fallot. The effective preservation of the native valve was impossible in all patients because of either a severe valve deformity or a small annulus. The RAA valve was created after ventricular septal defect closure and right ventricular outflow tract myectomy and was covered with a bovine transannular pericardial patch. The perioperative data were evaluated, and the echocardiography results were assessed immediately after operations and in follow-up with a median of 10.5 months. The data were retrospectively compared with 10 other patients with similar demographic data but with only transannular patches. RESULTS: The mean age of the patients was 13.3 months. No mortality or related morbidity occurred after repair using the RAA valve. The PI severity early after the operation was trivial or no PI in 18 patients, and mild PI was observed in 3 patients, which progressed to moderate PI in one of them in the mean 12-month follow-up period. Fifteen patients had mild or no pulmonary stenosis, while moderate pulmonary stenosis was observed in 6 others. Compared with the other 10 patients with only transannular patches, the RAA valve patients had prolonged operative and clamping times, but no difference in postoperative course and shorter hospital stays. The degree of PI was, of course, significantly less in the RAA valve patients, but pulmonary stenosis was the same. CONCLUSIONS: The RAA valve construction is a safe and effective technique to prevent PI after the tetralogy of Fallot repair, at least in terms of short- and mid-term results. A longer follow-up period is needed to confirm if this new valve can eliminate or significantly delay the need for pulmonary valve replacement in these patients.